ICT as pedagogical support in chemistry teaching: teacher training possibilities and student inclusion (Research, Society and Development, 2020)
Discussion about including education is necessary when it is understood that each child and young person has their own educational needs. Thus, the teacher is given the role of seeking different teaching methodologies that encourage their students to learn and actively participate in the educational process. When approaching teaching methodologies that provide inclusion, we have classes using technologies. It is understood, then, that there is a need to train teachers to exercise their profession in a globalized and technological society, making use of current technologies to improve their teaching practice, in a didactic manner and focused on learning and intellectual, social and cultural development of the students. In this context, the aim of this paper is to propose a short course on including teaching with the use of ICT for undergraduate students in chemistry. In this work, a short course on ICT and including education for undergraduates in Chemistry was created using references, texts on the theme including education and technologies and software and applications that can help in some way the inclusion of students in classes. Chemistry. The proposed short course attempts to minimize the effects of the scarcity of inclusive education technology training in higher education institutions, undergraduate chemistry courses and provides future teachers with scientific and practical knowledge about including education and the application of including teaching methodologies. using current technologies.